Ways to increase the financial and economic efficiency of investments - Khujakulova Nigora Rustamovna,; Kodirova Mokhinur Bakhodir kizi, (THE INNOVATION ECONOMY, 2026)
This article discusses the financial and economic efficiency of investments, the effective use of investments, income from investments and their positive impact on the economy. Also, the problems and shortcomings in increasing the economic efficiency of investments and investment activities are analyzed, and proposals and recommendations are given to increase their financial and economic efficiency.